If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5 = 5x + 8 Reorder the terms: 5 + 6x = 5x + 8 Reorder the terms: 5 + 6x = 8 + 5x Solving 5 + 6x = 8 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 5 + 6x + -5x = 8 + 5x + -5x Combine like terms: 6x + -5x = 1x 5 + 1x = 8 + 5x + -5x Combine like terms: 5x + -5x = 0 5 + 1x = 8 + 0 5 + 1x = 8 Add '-5' to each side of the equation. 5 + -5 + 1x = 8 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = 8 + -5 1x = 8 + -5 Combine like terms: 8 + -5 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| -3(m-6)=-6 | | 2(x-4)5x=7 | | 6x+18=28-4x | | 3x-32=2(40-x) | | 4x+58=10+13 | | n^2+n+92=0 | | 3g=8-7g | | 34+13x=30+22x | | 0.9x-0.3(6-x)=2.4 | | n/10=3/5 | | pn=55 | | 13=-3(21-b)+2(b-2) | | 10x+7=4x-31 | | -4=2(d-3)-8 | | 0=15-3y-7x | | 9z+2-7z=56-7z | | 6x-32=2(40-x) | | -15k+9k=25 | | 2(s+2)+1=9 | | 11(z+3)-4(z-3)=3(z-4)+3(z-4) | | -61n-8=-8 | | 3y+1=x+4 | | 7x+7-8x=3x-3+x | | 5-u=10 | | 3x+4=44-2x | | 2h-h+5=19 | | 6x^3-36x^2-16x+3=0 | | -7a-3=-4a+7 | | 2x+3.3=8.1 | | 3(x+1)+2x=-2x-4(2x+3) | | 13=-7+6x | | x+5/8=(x/4)+(5/12) |